Malliavin calculus for difference approximations of multidimensional diffusions: Truncated local limit theorem - Kulik, A.M. (Український математичний журнал, 2008)
For difference approximations of multidimensional diffusions, the truncated local limit theorem is proved. Under very mild conditions on the distributions of difference terms, this theorem states that the transition probabilities of these approximations, after truncation of some asymptotically negligible terms, possess densities that converge uniformly to the transition probability density for the limiting diffusion and satisfy certain uniform diffusion-type estimates. The proof is based on a new version of the Malliavin calculus for the product of a finite family of measures that may contain non-trivial singular components. Applications to the uniform estimation of mixing and convergence rates for difference approximations of stochastic differential equations and to the convergence of difference approximations of local times of multidimensional diffusions are given. Для різницєвих наближень багаroвимiрних дифузій доведено локальну граничну теорему зі зрізанням. При дуже слабких умовах на розподіли різницевих членів ця теорема стверджує, що ймовірності переходу таких наближень після видалення певних доданків, якими в асимптотичному сенсі можна знехтувати, мають щільності, які рівномірно прямують до щільності ймовірності переходу граничної дифузії та задовольняють певні рівномірні оцінки дифузійного типу Доведення базується на новому варіанті числення Маллявена для добутку скінченної сім'ї мір, які можуть містити нетривіальні сингулярні компоненти. Наведено застосування до рівномірного оцінювання коефіцієнта перемішування та швидкості збіжності для різницевих наближень стохастичних диференціальних рівнянь та до збіжності різницевих наближень локальних часів багатовимірних дифузій.